Ekonomiska konsekvenser av etanolproduktion i östra Sverige - Flensén, Andreas (2006)
This study analyses the economic consequences due to ethanol production in Eastern Sweden. The analyses consider the cooperative and the farmers as one vertically integrated company. The area that found the market in this study is illustrated in figure 1.